(untitled) (Revista Ciência Agronômica, 2015)
The aim of this study was to determine the uniformity trial size when estimating optimum plot size in order to evaluate fresh phytomass in lettuce plants and fruit weight in sweet peppers. Production data, collected in uniformity trial on lettuce in a plastic greenhouse in both summer and winter, lettuce in plastic tunnels in autumn and winter, and sweet pepper in a plastic greenhouse in the summer-autumn and spring-summer seasons, were used to plan different uniformity trial sizes in crop rows. In all the experiments, each plant was evaluated individually and considered as a basic experimental unit. For each size in a uniformity trial, 3,000 resamples, randomly taken with replacement, were used to estimate optimum plot size. Uniformity trial using 27 basic experimental units to evaluate the fresh phytomass of lettuce plants, and with 29 basic experimental units to assess fruit weight in sweet pepper, are sufficient to estimate optimum plot size, with an amplitude of the 95% confidence interval of less than or equal to two basic experimental units.